Investigation of environment parameters and metal corrosion rate n atmospheric enviroment at Phan Thiet - none, Văn Sơn; Phạm Hồng Thạch; Phạm Thanh Hải; none, Trọng Cường (Journal of Military Science and Technology, 2022)
The paper presented the results of determining the deposition rate of chloride and sulfur dioxide, the parameters of temperature, humidity and corrosion rate of carbon, copper, aluminum, zinc in the outside area and in the warehouse at X unit where was stationed in the area of ​​Phan Thiet. The results showed that the deposition rate of chloride and sulfur dioxide in outdoor and warehouse areas are quite low. However, the time of wetness in the two locations is significant difference, and the metal corrosion rate also had many differences.On the basis of the obtained data, it was possible to classify the atmospheric corrosion activity of Phan Thiet according to ISO 9223:2012. According to this Standard, the atmospheric environment of Phan Thiet in the outdoor area was classified into group S1 for chlorine deposition, group P1 for sulfur dioxide deposition, and group T4 for time of wetness. According to Standard 9226: 2012 classification of group C3 for steel corrosion rate, group C5 for copper corrosion rate, group C4 for aluminum corrosion rate, group C3 for zinc corrosion rate.